Co-occurrence networks reveal candidate AMF–microbe assemblages for generalist and crop-specific inocula - Mathieu Delaeter; Papa Mamadou Sitor Ndour; Benoit Tisserant; Béatrice Randoux; Lobna Abdellatif; Franck Stefani; Maryline Magnin-Robert; Anissa Lounès-Hadj Sahraoui (Mycorrhiza, 2026)
Arbuscular mycorrhizal fungi (AMF) are widespread root symbionts increasingly used as bioinoculants. Because symbiotic efficiency depends on interactions with other plant-beneficial microbes, identifying compatible taxa and positive interaction patterns across hosts and niches could improve the design of crop-specific AMF-based inocula. Using amplicon sequencing and co-occurrence network analyses, microbial communities (AMF, fungi and bacteria) from the rhizosphere and roots of wheat were characterized and compared with those of two highly mycotrophic plant species: leek (monocotyledon) and clover (dicotyledon). Results showed that AMF diversity associated with wheat roots was 1.37- and 1.24-fold lower than that observed in leek and clover, respectively. Across all plant species, Glomus and Rhizophagus taxa dominated root-associated communities, whereas Diversispora prevailed in the rhizosphere. In contrast, wheat harboured the highest bacterial and fungal richness compared with leek and clover, whereas leek and clover roots were enriched in several functional bacterial groups, including nitrogen-fixing bacteria, denitrifying and nitrifying bacteria and plant growth promoting bacteria. Co-occurrence network analyses revealed niche partitioning with bacterial interactions predominant in roots and fungal interactions in the rhizosphere, but with fewer and less-positive connections in wheat than in leek and clover. AMF showed positive associations with beneficial bacterial taxa (e.g. Rhizobium , Pseudomonas , Streptomyces ) and fungal taxa (e.g. Serendipita ), with interaction patterns varying among plant species. Together, these results demonstrate that plant identity and niche jointly shape the diversity and interaction patterns of root and rhizosphere-associated microbial communities, and they highlight specific AMF-microbe assemblages as promising candidates for the development of generalist or crop-specific AMF-based inocula.

Different temperature responses of mountain rockwalls, soils, and lakes to summer heat waves - Rosalie Bruel; Florent Arthaud; Florence Magnin; Raphaëlle Napoleoni; Colin Van Reeth; Vincent Augé; Clotilde Sagot; Mathieu Fructus; Carole Birck; Philippe Choler (Regional Environmental Change, 2026)
Mountain ecosystems are highly sensitive to climate variations. At fine spatial scales, high-elevation microclimates play a critical role in shaping biodiversity, hydrological processes, and ecosystem services, while also influencing the occurrence of natural hazards such as landslides, avalanches, and floods. Heat waves, which have been increasing in frequency and intensity due to global climate change, present significant challenges to these vulnerable environments. This study examines the impacts of summer heat waves on mountain microthermal conditions in three compartments: rockwalls, soils, and lakes. We assembled data across a latitudinal and elevational gradient in the French Alps including years of two recent heat wave events (2015 and 2022). We calculated thermal indicators to evaluate the buffering or amplifying effects of the atmospheric signal on the investigated compartments. The average summer temperature and the growing/thawing degree days were more responsive to heat waves than the phenological indicator (e.g., spring mixing date in lakes) and maximum temperature. We found significant anomalies for both the 2015 and 2022 heat waves across almost all compartments and indicators. Lakes tended to amplify atmospheric temperatures (especially in 2022) whereas rockwalls and soils tended to buffer them. However, residues from the relationship between compartment and atmospheric temperatures were large during heat waves, suggesting that these events may reduce the compartments’ buffering capacity. Our study underscores the importance of long-term monitoring of microthermal conditions to provide a more integrative assessment of mountain ecosystem response to extreme meteorological events. Graphical abstract

Infrared pupillometry to measure pupil light reflex in awake cats: Feasibility and evaluation pre- and post-opioid administration - Mathieu Magnin; Léa Goffette; Stéphane Junot; Jeanne Marie Bonnet-Garin; Bernard Allaouchiche; Céline Pouzot-Nevoret (Research in Veterinary Science, 2026)

Indirect assessment of autonomic nervous system balance for prediction of hemorrhage: A preclinical study in a porcine model - Mathieu Magnin; Amandine Chapelle; Stéphane Junot; Bernard Allaouchiche; Timothée Schuhler; Romain Lac; Valentin Bondoux; Guillaume L. Hoareau; Mark Kim; Tatiana Victoni; Céline Pouzot-Nevoret (Research in Veterinary Science, 2025)

Modeling the relationship between arterial blood pressure and sublingual microcirculatory blood flow assessed by Sidestream Dark Field videomicroscopy: An experimental study in anesthetized piglets. - Élisa Foulon; Jeanne-Marie Bonnet-Garin; Bernard Allaouchiche; Stéphane Junot; Mathieu Magnin (Research in Veterinary Science, 2023)

Use of pupillometry for the evaluation of analgesia in dogs hospitalized in intensive care: A prospective study - Céline Pouzot-Nevoret; Stéphane Junot; Léa Goffette; Jeanne-Marie Bonnet-Garin; Bernard Allaouchiche; Mathieu Magnin (Research in Veterinary Science, 2023)